1998
DOI: 10.1006/anbo.1997.0543
|View full text |Cite
|
Sign up to set email alerts
|

Maturation and Ripening of Fruit ofAmelanchier alnifoliaNutt. are Accompanied by Increasing Oxidative Stress

Abstract: The extent of oxidative stress during ripening of saskatoon (Amelanchier alnifolia Nutt.) fruit was examined. Lipid peroxidation during fruit development from the mature green to the fully ripe (purple) stage was evidenced by the accumulation of ethane and 2-thiobarbituric acid reactive substances. Fruit polar lipid and free fatty acid concentrations also declined during ripening. Moreover, the double bond index of fatty acids in the polar lipid fraction fell during ripening, reflecting a progressive increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 53 publications
5
72
1
Order By: Relevance
“…During ripening, a variety of physical and biochemical mechanisms change the structure of cell walls in fleshy fruits with textural results ranging from crisp to melting or soft and deformable (Brummell 2006).The deterioration of plant membranes during senescence is well documented and several enzymes are involved (Paliyath and Droillard 1992). Research has focussed on the post harvest period, but interestingly, enzymes of the lipoxygenase family have been associated with membrane lipid peroxidation in ripening saskatoons (Rogiers et al 1998) and volatile aroma or flavour development in tomatoes (Chen et al 2004) and kiwifruit (Zhang et al 2006a). It has been noted that aroma compounds in wine grapes increase late in ripening when sugar accumulation has slowed or stopped and non-anthocyanin glycosides rise sharply at around 100 DAA in Shiraz (Coombe and McCarthy 1997).…”
Section: Discussionmentioning
confidence: 99%
“…During ripening, a variety of physical and biochemical mechanisms change the structure of cell walls in fleshy fruits with textural results ranging from crisp to melting or soft and deformable (Brummell 2006).The deterioration of plant membranes during senescence is well documented and several enzymes are involved (Paliyath and Droillard 1992). Research has focussed on the post harvest period, but interestingly, enzymes of the lipoxygenase family have been associated with membrane lipid peroxidation in ripening saskatoons (Rogiers et al 1998) and volatile aroma or flavour development in tomatoes (Chen et al 2004) and kiwifruit (Zhang et al 2006a). It has been noted that aroma compounds in wine grapes increase late in ripening when sugar accumulation has slowed or stopped and non-anthocyanin glycosides rise sharply at around 100 DAA in Shiraz (Coombe and McCarthy 1997).…”
Section: Discussionmentioning
confidence: 99%
“…LOX action passes through the peroxidation of polyunsaturated fatty acids and the formation of a class of end-products known as oxylipins which have specific functions in signaling and plant defense responses (Nooden and Leopold 1988;Rogiers et al 1998;Zhang et al 2006). It was observed that in senescing tissues and during the ripening of some fruits there is a clear relationship between lipid peroxidation and increasing oxidative levels (Rogiers et al 1998;Brennan and Frenkel 1977;Brennan et al 1979). This suggests that, although LOX are involved in different activities, for some of them the expression during grape ripening could be linked to the oxidative burst occurring in berries around vĂ©raison.…”
Section: Abiotic Stresses Response Proteinsmentioning
confidence: 99%
“…During the life cycle, plants overcome genetically regulated processes that lead to the production of ROS such as senescence (Kukavica and Jovanovic 2004) and ripening. Ripening, described as an oxidative process (Brennan and Frenkel 1977, JimĂ©nez et al 2002a, JimĂ©nez et al 2002b, Rogiers et al 1998, is accompanied by changes in flavor, texture, color, and aroma. Climacteric fruits such as tomato also show a burst of ethylene biosynthesis and an increase in respiration during ripening (White 2002).…”
Section: Introductionmentioning
confidence: 99%